Lucifer in harness : American meter, metaphor, and diction - Fussell, Edwin S. ([Princeton, New Jersey] : Princeton University Press, 1973)
For nearly two hundred years the rebellious American poet has been reluctantly harnessed to the English language and literary tradition. In a triptych of essays, Edwin Fussell attempts ""to explore the fundamental dilemma of American poetry as it appears in the three crucial fields of meter, metaphor, and poetic diction, the three crucial fields of American poetry (taken as a whole) most studiously avoided by American scholars, but not, as I intend to show, by American poets."" Writing in a provocative critical style attuned to the poets he discusses, Edwin Fussell explores the dilemma of t.
Preface; 1: The Meter-Making Argument; 2: The Constituting Metaphor; 3: What the Thunder Said.
Print version record.
eBooks on EBSCOhost
Keywords: American poetry -- History and criticism; Poésie américaine -- Histoire et critique; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM -- Poetry; American poetry; Criticism, interpretation, etc